STUDY OF THE PSYCHO-EMOTIONAL CONDITION AND WORKING ABILITY OF MEDICAL STUDENTS - Deyana Todorova; Albena Andonova; Petya Hristova; Magdalena Platikanova (Science & Research)

(untitled)
The training of students majoring in "medical assistant", "nurse" and "medicine" is one of the most responsible and is associated with great mental and physical stress. Various factors affect students during their studies and one of them is psycho-emotional stress, which is significantly manifested in clinical practice. In their course of study, students must acquire theoretical knowledge and practical skills in the relevant specialty, but must also be familiar with the mechanisms of action of stress and be trained to recognize it to deal with it at an early stage. Specialized training for stress is not included in the curricula of students, and it would be one of the main and decisive methods for prevention of mental and physical consequences of stress in the workplace afterward. The study showed that students should be aware of workplace stress, which affects their psycho-emotional state and ability to work. Awareness is essential for the smooth performance of their future work as medical professionals, because the work of medical professionals is directly related to patients, their relatives, and colleagues, and these interpersonal relationships often affect the psycho-emotional state and ability to work.